Răspuns :
O(0;0)⇒f(0)=0
f(0)=b⇒b=0
M(-1;-3)⇒f(-1)=-3
f(-1)=-a+0=-a⇒-a=-3⇒a=3
f(x)=3x
f(0)=b⇒b=0
M(-1;-3)⇒f(-1)=-3
f(-1)=-a+0=-a⇒-a=-3⇒a=3
f(x)=3x
Daca M(-1;-3) atunci f(-1) = -3
adica a (-1) + b = -3
rezulta -a + b = -3
coordonatele punctului O sunt (0;0)
rezulta f(0) = 0
adica a * 0 + b = 0
deci b = 0
il inlocuim pe b=0 in ecuatia -a + b = -3
si rezulta
-a + 0 = -3
deci -a = -3
a = 3
raspunsurile sunt :
a=3
b=0
adica a (-1) + b = -3
rezulta -a + b = -3
coordonatele punctului O sunt (0;0)
rezulta f(0) = 0
adica a * 0 + b = 0
deci b = 0
il inlocuim pe b=0 in ecuatia -a + b = -3
si rezulta
-a + 0 = -3
deci -a = -3
a = 3
raspunsurile sunt :
a=3
b=0